A case of recurrent swimming‐induced pulmonary edema in a triathlete: the need for awareness. (3rd August 2016) - Smith, R.; Brooke, D.; Kipps, C.; Skaria, B.; Subramaniam, V.
Abstract : This report discusses a rare case of a 55‐year‐old female triathlete who developed recurrent episodes of swimming‐induced pulmonary edema (SIPE). She had two hospital admissions with pulmonary edema after developing breathlessness while swimming, including a near‐drowning experience in an open water swim. With increasing popularity of triathlon and open water sports, this case highlights the importance of a greater awareness of SIPE among health professionals, event organizers, and athletes. This report explores the previous reported cases in triathletes and those who have suffered recurrent episodes. It is paramount that an accurate diagnosis is made as these individuals may be at an increased risk of future life‐threatening episodes.